Study of Flow Characteristics Over a Rounded Edge Drop Structure in Open Channel - Kori, S. M.; Mahessar, A. A.; Channa, M.; Memon, A. A.; Kori, A. R. (Engineering, Technology & Applied Science Research, 2019)
Flow over a drop structure is a form of free overfall called hydraulic drop. Hydraulic drop changes the nature of flow abruptly from sub-critical to super-critical condition. Rapidly varied flow analysis is a complex phenomenon and involves remarkable characteristics. Some of the drop structures constructed in Sindh and Punjab provinces of Pakistan had gone through diverse failures, consequential in interruption of water supply to irrigation fields encountering substantial economic loss. In the present study experiments were carried out in the hydraulic laboratory of Mehran University of Engineering and Technology on round edged drop structure fitted in a horizontal rectangular flume (channel model). Data regarding hydraulic drop and hydraulic jump characteristics were collected during the experiment. The observed data included: flow discharge (Q), radius of rounded edge drop structure (r), height of the structure (h), hydraulic drop length (Ld), hydraulic jump length (Lj), depth of flow at toe of the jump (Y1) and tailwater depth (Y2). Applying dimensional analysis, the non-dimensional parameters of the observed data were calculated. Using statistical analysis, empirical relationships among the non-dimensional parameters were established for the appropriate design of the drop structure. The research results showed that the length and depth indices are functions of D=q2gh3 and r/h values. It was also found that for rounded-edge drop structure, the length of the stilling basin (LSB) reduces as r/h ratio increases